Effect of Supplementing Moringa oleifera and Organic Acid on the Haemato-Biochemical Parameters of Broilers - Neha; V. Sharma; D. S. Bidhan; Sweety, Amandeep; D. Dangi (Indian Journal of Animal Nutrition, 2024)
The present study was conducted to investigate the effect of supplementing Moringa oleifera and organic acid on the haemato-biochemical performance of broilers. Two hundred and twenty-five, day-old unsexed broiler chicks were used on a completely randomized design in four groups with three replicates, each consisting of 15 broiler chicks. The treatments included the T0 group (negative control i.e. basal ration without antibiotic), T1 group (control i.e. basal ration with antibiotics), T2 group (basal Ration + 1% M. oleifera), T3 group (basal Ration + 0.5 % Organic acid) and T4 group (basal Ration + 1% M. oleifera + 0.5% Organic acid). The haemato-biochemical parameters were studied after the end of the trial. The results of the present study showed that supplementation of Moringa oleifera, Organic acid alone and in combination did not affect the hematological indices viz. Hb, PCV, TLC, DLC in broiler chickens. The cholesterol, triglycerides, HDL and LDL content of chicken broilers were significantly improved in group supplemented withcombination of Moringa oleifera and Organic acid (T4).Therefore, it can be concluded that 1% Moringa oleifera alone, 0.5% Organic acid alone or combination of both can be effectively supplemented to improve serum biochemical parameters of broiler chicken ration without any adverse effect on survivability of birds.